Basic Human Rights Instruments in the Perspective of International and National Law - Hairul Anam; Maslathif Dwi Purnomo (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
Human rights are fundamental rights inherent to every individual by virtue of being human and constitute the foundation of justice, equality, and human dignity. The protection and promotion of these rights require comprehensive legal instruments at both the international and national levels to ensure their effective implementation. This study aims to examine the fundamental instruments of human rights, analyze their legal foundations, and evaluate the mechanisms for human rights protection and enforcement in Indonesia. The research employs a normative legal approach based on literature review, utilizing secondary data derived from legal documents, scholarly publications, and relevant legal theories. The collected data were analyzed descriptively and qualitatively through a systematic examination of international and national legal frameworks. The findings reveal that human rights protection is supported by two principal categories of legal instruments: international instruments, including the Universal Declaration of Human Rights (UDHR), the International Covenant on Civil and Political Rights (ICCPR), the International Covenant on Economic, Social and Cultural Rights (ICESCR), and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW); and national instruments, including the 1945 Constitution, Pancasila, Law No. 39 of 1999 on Human Rights, and other relevant legislation. Indonesia has also established specialized institutions, such as the National Commission on Human Rights (Komnas HAM), the Human Rights Court, the Indonesian Child Protection Commission (KPAI), the National Commission on Violence Against Women (Komnas Perempuan), and the Witness and Victim Protection Agency (LPSK), to strengthen human rights enforcement. Nevertheless, significant challenges remain, including weaknesses in law enforcement, institutional effectiveness, and the protection of vulnerable groups. Therefore, strengthening legal institutions, harmonizing international and national human rights standards, and enhancing the capacity of enforcement agencies are essential to ensuring comprehensive and effective human rights protection in Indonesia.